Disruption of biological membranes by hydrophobic molecules: a way to inhibit bacterial growth - Valdez-Lara, Alejandra Gabriela; Jaramillo-Granada, Ángela M.; Ortega-Zambrano, Daniel; García-Marquez, Eristeo; García-Fajardo, Jorge Alberto; Mercado-Uribe, H.; Ruiz-Suárez, J. C. (Frontiers in Microbiology, 2025)
With antibiotic resistance increasing in the global population every year, efforts to discover new strategies against microbial diseases are urgently needed. One of the new therapeutic targets is the bacterial cell membrane since, in the event of a drastic alteration, it can cause cell death. We propose the utilization of hydrophobic molecules, namely, propofol (PFL) and cannabidiol (CBD), dissolved in nanodroplets of oil, to effectively strike the membrane of two well-known pathogens: Escherichia coli and Staphylococcus aureus. First, we carried out calorimetric measurements to evaluate the effects of these drugs on model membranes formed by lipids from these bacteria. We found that the drugs modify their transition temperature, enthalpy of cohesion, and cooperativity, which indicates a strong alteration of the membranes. Then, inhibition of colony-forming units is studied in incubation experiments. Finally, we demonstrate, using atomic force and fluorescence microscopy, that the drugs, especially propofol, produce a visible disruption in real bacterial membranes, explaining the observed inhibition. These findings may have useful implications in the global effort to discover new ways to effectively combat the growing threat of drug-resistant pathogens, especially in skin infections.